Effect of Media Synchronization Module on Learning Achievement of the Software Engineering Students of Vocational High School - Agus, Muhammad Chusni; Mukhadis, Amat; Sutadji, Eddy (Journal of Education and Vocational Research, 2017)
This research aims at examining the effect of media synchronization module, mechanical aptitude, and prior knowledge on learning achievement of eleven grade students of the Software Engineering (RekayasaPerangkatLunak/RPL) Programin Vocational High School 5 at Malang, East Java, Indonesia. This quasi-experimental research used factorial design of 2x2x2 pattern and applied the non-equivalent control group design. It involved 74 students who were divided into two groups; 37 students were in the experimental group and 37 students were in the control group. Tests were used to investigate the students’ mechanical aptitude, prior knowledge and learning achievement. Data were analyzed by using three-way ANOVA. The results of the research showed that: 1) There was a significant difference in the learning achievement of the group taught by using media synchronization module and those who were taught by using the conventional method; 2) there was no significant difference in the learning achievement in the C++ Programming between students who had high and low mechanical aptitude; 3) there was a significant difference in the learning achievement in C++ Programming between students who had high and low prior knowledge; and 4) there was no significant interaction among media synchronization module, mechanical aptitude, and prior knowledge on the learning achievement with C++ Programming.